Improving complementary feeding in low- and middle-income countries: a review of crayfish’s nutritive and health values - Adegbusi, Halid S; Ismail, Amin; M Esa, Norhaizan; Daud, Zulfitri AM; Shukri, Nurul HM (Elsevier, 2024)
This review elucidated the nutritive and health benefits of crayfish to encourage the consumption during complementary feeding among poor households in low- and middle-income countries (LMICs). Crayfish contained high-quality nutrients that may complement poor traditional complementary foods (CFs) for child growth and development. Crayfish had high contents of about 64.14% protein, 10.5 g/100 g of crude protein of sulfur–amino acids, low contents of about 9.12% and 5.45% of lipid and carbohydrate (CHO) respectively, and a substantial ratio of n-3/n-6, 6.41. CFs formulated from plant-based foods (PBFs) and crayfish were found to be of high quality and nutritious value. The astaxanthin content may improve organoleptic qualities of CFs and health status of individual consumers. Introduction of crayfish diet during complementary feeding may lower undernutrition among children in LMICs.